A Genomic, Evolutionary, and Mechanistic Study of MCR‐5 Action Suggests Functional Unification across the MCR Family of Colistin Resistance. Issue 11 (3rd April 2019) - Zhang, Huimin; Zong, Zhiyong; Lei, Sheng; Srinivas, Swaminath; Sun, Jian; Feng, Yu; Huang, Man; Feng, Youjun
Abstract: A growing number of mobile colistin resistance (MCR) proteins is threatening the renewed interest of colistin as a "last‐resort" defense against carbapenem‐resistant pathogens. Here, the comparative genomics of a large plasmid harboring mcr‐5 from Aeromonas hydrophila and the structural/functional perspectives of MCR‐5 action are reported. Whole genome sequencing has identified the loss of certain parts of the Tn 3 ‐type transposon typically associated with mcr‐5, providing a clue toward its mobilization. Phylogeny of MCR‐5 suggests that it is distinct from the MCR‐1/2 sub‐lineage, but might share a common ancestor of MCR‐3/4. Domain‐swapping analysis of MCR‐5 elucidates that its two structural motifs (transmembrane domain and catalytic domain) are incompatible with its counterparts in MCR‐1/2. Like the rest of the MCR family, MCR‐5 exhibits a series of conservative features, including zinc‐dependent active sites, phosphatidylethanolamine‐binding cavity, and the mechanism of enzymatic action. In vitro and in vivo evidence that MCR‐5 catalyzes the addition of phosphoethanolamine to the suggestive 4′‐phosphate of lipid A moieties is integrated, and results in the consequent polymyxin resistance. In addition, MCR‐5 alleviates the colistin‐induced formation of reactive oxygen species in E. coli . Taken together, the finding suggests that a growing body of MCR family resistance enzymes are functionally unified. Abstract : An mcr‐5 ‐containing plasmid from the zoonotic pathogen Aeromonas hydrophila is reported. Comparative genomics suggests that mcr‐5 disseminates via Tn 3 transposon‐based genetic events. Despite its being evolutionarily different from MCR‐1/2, the biochemical and physiological characterization of MCR‐5 strongly displays functional unification across the entire mobile colistin resistance family.